OPTIMALISASI PERAN RADAR SUKABUMI SEBAGAI MEDIA EDUKASI PUBLIK BERBASIS NILAI-NILAI KEISLAMAN - Yulistiana; Siti Afwa Salima; Siti Sarah; Muhamad Nizar; Muhammad Rizqi Fauzi; Muhamad Alvin Fauzan F (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze and formulate strategies to optimize the role of Radar Sukabumi, a leading local media outlet in West Java, as a public education platform based on Islamic values. As a region with a strong Islamic boarding school (pesantren) base, the Sukabumi community has a strong religiosity, necessitating a contextual approach to media education. The research method used was descriptive qualitative with a case study approach. The results indicate that Radar Sukabumi has played a role in disseminating Islamic-themed information. However, further optimization is needed, particularly in the development of educational digital content and the integration of Islamic values (such as rahmatan lil 'alamin, religious moderation, and social ethics) into each news column. Optimizing this role is expected to foster polite and educative public literacy amidst the flow of digital information.